Експериментальність українського роману 20-х років XX століття - Сайковська, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is dedicated to the phenomenon of the experimental prose in the 20’s of the XX century that was not investigated for century. The artistic experiment is treated as a leading trend of the prose of that period. Novels by Majk Johansen «Doctor-scientist Leonardo and his future lover beautiful Alchesta’s trip to Slobozhanska Switzerland», Mychajlo Yalovuy «Golden foxes» («Zoloti lysenyata») and Jurij Janovskuy «Master of the ship» are characterized by modifications in genre and style. Their experimental features reveal themselves on different textual levels. Communicativeness, co-creation of modernist work by the author and the reader, the concept of reality as a game and so-called «selfreflexive» literature – are important on all text levels.